Steeper Iris Conicity Is Related to a Shallower Anterior Chamber: The Gutenberg Health Study. (11th September 2017) - Schuster, Alexander K.; Pfeiffer, Norbert; Nickels, Stefan; Schulz, Andreas; Wild, Philipp S.; Blettner, Maria; Lackner, Karl; Beutel, Manfred E.; Münzel, Thomas; Vossmerbaeumer, Urs
Abstract : Purpose . To report the distribution of iris conicity (steepness of the iris cone), investigate associated factors, and test whether pseudophakia allows the iris to sink back. Methods . A population-based cross-sectional study was carried out. Ophthalmological examination including objective refraction, biometry, noncontact tonometry, and Scheimpflug imaging (Pentacam®, Oculus) was performed including automated measurement of iris conicity. 3708 phakic subjects, 144 subjects with bilateral and 39 subjects with unilateral pseudophakia were included. Multivariable analyses were carried out to determine independently associated systemic and ocular factors for iris conicity in phakic eyes. Results . Mean iris conicity was 8.28° ± 3.29° (right eyes). Statistical analysis revealed associations between steeper iris conicity and shallower anterior chamber depth, thicker human lens and higher corneal power in multivariable analysis, while older age was related to a flatter iris conicity. Refraction, axial length, central corneal thickness, pupil diameter, and intraocular pressure were not associated with iris conicity. Pseudophakia resulted in a 5.82° flatter iris conicity than in the fellow phakic eyes. Conclusions . Associations indicate a correlation between iris conicity with risk factors for angle-closure, namely, shallower anterior chamber depth and thicker human lens. In pseudophakic eyes, iris conicity is significantly lower, indicating that cataract surgery flattens the iris.